2024
DOI: 10.1186/s12964-023-01398-5
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of oxidative stress, cellular communication and signaling pathways in cancer

Muhammad Javed Iqbal,
Ayesha Kabeer,
Zaighum Abbas
et al.

Abstract: Cancer remains a significant global public health concern, with increasing incidence and mortality rates worldwide. Oxidative stress, characterized by the production of reactive oxygen species (ROS) within cells, plays a critical role in the development of cancer by affecting genomic stability and signaling pathways within the cellular microenvironment. Elevated levels of ROS disrupt cellular homeostasis and contribute to the loss of normal cellular functions, which are associated with the initiation and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 107 publications
1
10
0
Order By: Relevance
“…At low levels of cellular ROS, p21 is known to stimulate a cytoprotective response dependent on NRF2. On the other hand, at elevated ROS levels, p21 inhibited the NRF2 activity, ultimately leading to cellular apoptosis [42]. Our results are supported by a recently published study by Acquaviva et al [43], who found that protocatechuic acid induced apoptosis in colon cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…At low levels of cellular ROS, p21 is known to stimulate a cytoprotective response dependent on NRF2. On the other hand, at elevated ROS levels, p21 inhibited the NRF2 activity, ultimately leading to cellular apoptosis [42]. Our results are supported by a recently published study by Acquaviva et al [43], who found that protocatechuic acid induced apoptosis in colon cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…Oxidative stress can lead to gene mutations, including those in tumor suppressor genes that control cell growth and prevent uncontrolled cell division. DNA damage by ROS and RNS can promote the accumulation of mutations, a crucial step in cancer development ( 53 ). Moreover, oxidative stress can affect inflammatory processes, which are also linked to the development of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a strict interplay between MMP levels and ROS production [38]. ROS activate signaling pathways that are involved in the transcriptional activation of the gene that promotes MMP expression (Figure 7) [39].…”
Section: Discussionmentioning
confidence: 99%